The Hungarian footwear industry in global production networks: the case study of Berkemann Hungary - Molnár, Ernő; Lengyel, István Máté (Acta Geographica Debrecina Landscape & Environment series, 2016)
The highly internationalized, labour-intensive footwear industry showed two spectacular declines and significant restructuring in Hungary after the change of regime. In accordance with the approach the authors investigate, this phenomenon is associated with the integration ways and circumstances of the industry into global production networks. Sector-level assessment of the processes – including the changing geographical patterns of footwear industry which also indicate features of path-dependence – was performed in several previous works of the authors. On the basis of significant empirical fieldwork, recent study focuses on the current situation of an extraordinary foreign owned large company representing the challenges and development perspectives Hungarian footwear industry has to face with.